Low carbon development and poverty alleviation: Options for development cooperation in energy, agriculture and forestry - Mikkel Funder; Jacob Fjalland; Helle Munk Ravnborg; Henrik Egelyng (Danish Institute for International Studies (DIIS), 2009)
This report presents the main findings from a desk study on “Climate change mitigation and poverty reduction in developing countries: opportunities for development cooperation.” The study identifies practical options for combining low carbon development with poverty reduction and economic growth in least developed countries, with a focus on energy, agriculture and forestry. The report also focuses on practical recommendations.
Keywords: 300; Klimaschutz; Entwicklungskooperation; Armutspolitik; Energiewirtschaft; Landwirtschaft; Forstwirtschaft; Entwicklungsländer